Listening to Parents of Children With Cancer—Between Life and its end. (June 2022) - Manor-Binyamini, Iris; Schreiber-Divon, Michal
This study aimed to explore and provide an in-depth insight into the experience and perceptions of parents to children with cancer at the end of life (EOL). A sample of 15 parents of children (aged 2-18) with cancer participated in semi-structured interviews in an oncology department of an Israeli hospital. Data were analyzed using a phenomenological thematic analysis approach. The findings that emerged revealed: (a) the cultural aspect of the Israeli society of the importance of family and of the children within the family, (b) the parents' unique way of coping, of holding a dual awareness, and (c) emphasizing that hope and support are necessary components for parents' ability to cope with their child having terminal cancer, at the EOL. A number of important practical recommendations can be made for professionals treating child facing the EOL with cancer and their families. First, understanding the "double awareness" developed by parents of children facing with EOL cancer. Second, there is significance to bring the medical staff closer to the patient's bed, which is to say, training medical staff in open communication on this subject. Third, it is recommended to construct intervention programs that would accompany the whole family and not just the parents. Fourth, there is some necessity to train healthcare teams working in pediatric oncology wards and providing palliative care, to teach them how to help people hold on hope and to evaluate hope in parents of children at the EOL.